2017
DOI: 10.1002/gps.4818
|View full text |Cite
|
Sign up to set email alerts
|

Amotivation is associated with smaller ventral striatum volumes in older patients with schizophrenia

Abstract: We replicate and extend the finding of reduced VS volumes with greater amotivation. We demonstrate this relationship uniquely beyond the potential contributions of striatal D R blockade by antipsychotics. Elucidating the structural correlates of amotivation in schizophrenia may help develop treatments for this presently irremediable deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 67 publications
2
17
5
Order By: Relevance
“…Capitalizing on a sample of SZ patients exhibiting blunted VS BOLD activation related to apathy, the present study aimed to extend previous work on the relationship between structural VS abnormalities and the severity of apathy in schizophrenia. Although applying the same methodological approaches as two recently published studies (Caravaggio et al, 2018a;Roth et al, 2016), we could not replicate the previously observed association between apathy and reduced VS volume in a larger sample. Given the fact that we have found blunted VS activation related to apathy in the same dataset (Fig.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Capitalizing on a sample of SZ patients exhibiting blunted VS BOLD activation related to apathy, the present study aimed to extend previous work on the relationship between structural VS abnormalities and the severity of apathy in schizophrenia. Although applying the same methodological approaches as two recently published studies (Caravaggio et al, 2018a;Roth et al, 2016), we could not replicate the previously observed association between apathy and reduced VS volume in a larger sample. Given the fact that we have found blunted VS activation related to apathy in the same dataset (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…The negative findings of the present study raise the question whether differences in sample characteristics (compared to (Caravaggio et al, 2018a;Roth et al, 2016)) are able to explain the missing association between reduced VS volume and apathy. Relevant confounding factors are differences in age, duration of illness and antipsychotic medication dose (Amato et al, 2017;Haijma et al, 2013;Hashimoto et al, 2018;van Erp et al, 2016).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations